METHODS OF SYNTHESIS EIGHT-TELLURIUM-CONTAINING HETEROCYCLES WITH MORE HETEROATOMS - G. M. Abakarov (Вестник Дагестанского государственного технического университета: Технические науки)
In this article systematized and summarized data on the synthesis of neweight-embered tellurium-containing heterocycles and new preparative methods described above produce heterocyclic tellurium.